1995
DOI: 10.1002/elps.1150160194
|View full text |Cite
|
Sign up to set email alerts
|

Separation of eleven angiotensin II analogs by capillary electrophoresis with a nonionic surfactant in acidic media

Abstract: Eleven angiotension II analogs of same chain length were separated by capillary electrophoresis at pH 2.0 with 200 mM Tween 20. All compounds except one pair of angiotensin II ([Sar1, Gly8]- and [Sar1, Val5, Ala8]-angiotensin II) were baseline-separated, even in the case of peptides with about the same total charge. The migration order of the angiotensin II analogs were determined by the hydrophobicity of the amino acid as long as the difference between amino acids of two peptides is the conservative change. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In addition, several communications have appeared dealing with the use of both neutral and zwitterionic surfactants, but here too the accent was on micellar electrokinetic chromatography, i.e., on the ability of these compounds to modulate the separation of peptides (and in general of hydrophobic compounds), via adsorption/interaction of the analyte with the detergent micelle. Thus, Greve et al [67], Issaq et al [68], van de Goor et al [69] and Yeung and Lucy [70] have used zwitterionic surfactants for improving the separation of different peptide mixtures; Swedberg [71] adopted nonionic and zwitterionic detergents with heptapeptides; Matsubara et al [72] and Matsubara and Terabe [73] utilized Tween 20 and Polysorbate 20 for optimizing the separation of closely related angiotensin II analogues.…”
Section: Behavior Of Surfactantsmentioning
confidence: 99%
“…In addition, several communications have appeared dealing with the use of both neutral and zwitterionic surfactants, but here too the accent was on micellar electrokinetic chromatography, i.e., on the ability of these compounds to modulate the separation of peptides (and in general of hydrophobic compounds), via adsorption/interaction of the analyte with the detergent micelle. Thus, Greve et al [67], Issaq et al [68], van de Goor et al [69] and Yeung and Lucy [70] have used zwitterionic surfactants for improving the separation of different peptide mixtures; Swedberg [71] adopted nonionic and zwitterionic detergents with heptapeptides; Matsubara et al [72] and Matsubara and Terabe [73] utilized Tween 20 and Polysorbate 20 for optimizing the separation of closely related angiotensin II analogues.…”
Section: Behavior Of Surfactantsmentioning
confidence: 99%
“…As the components of bacitracin carry positive charge, it was found that the acidic buffer (pH 2.5) was essential to reduce the adsorption of the analyte on the capillary wall. In literature, PAPS [25] and nonionic surfactant [26,27] were found to be useful for the separation of peptides with closely related structures with MEKC. In the present case, it was found that PAPS offered a better selectivity than Brij 35.…”
Section: Methods Developmentmentioning
confidence: 99%
“…With peptides differing in hydrophobicity, the common approach to effect a separation is the implementation of a hydrophobic interaction by using micelles: zwitterionic, e.g., CHAPS [21]; neutral, e.g., Brij 35 [22], Tween 20 [23], octyl glucoside [24]; or charged [21]. Especially impressive was the separation by Fürtös-Matei et al [21] of 13 Ala-scan dynorphin analogues with CHAPS as additive.…”
Section: Hydrophobic Interaction Mechanism: Mekcmentioning
confidence: 99%